Identification and Evaluation of the Ways of Meeting Patients' Expectations from a Hospital: An AHP-Weighted QFD Case Study In A Pediatric Hospital - N. Özgür Doğan; Hazal Akbal (Istanbul Business Research (IBR), 2020)
The purpose of this study is to determine the expectations of pediatric patients from a hospital and find out feasible solutions to address these expectations. In accordance with this purpose, an AHP-weighted QFD case study was carried out in a pediatric hospital in Turkey. In order to determine the expectations of pediatric patients; face-to-face and semi-structured interviews were used and the natural environment of the hospital was observed in many different times. Expectations of the children constituted the left part of the House of Quality (HoQ) of QFD and were weighted using the AHP. Then, technical requirements offering solutions to expectations of children were defined, other parts of the house were added and the whole HoQ was completed. The results show that, from the children's point of view, accommodation services was found as the most important factor and arrangement of the patient rooms as the most important sub-factor. All remaining factors and sub-factors were also evaluated and prioritized. It is hoped that this study can contribute to the related literature and the QFD model developed in the study can be taken as an example by similar and/or different hospitals. Finally, the limitations of this study and future research directions are outlined.
Keywords: 650; Analytic hierarchy process; quality function deployment; pediatric hospital; patient provider communication; patient expectations